A review on schizophrenia and relapse—a quest for user‐friendly psychopharmacotherapy. (23rd July 2014) - Suzuki, Takefumi; Uchida, Hiroyuki; Takeuchi, Hiroyoshi; Tsuboi, Takashi; Hirano, Jinichi; Mimura, Masaru
<x xml:space="preserve">Abstract</x> Objective Schizophrenia in general is notoriously associated with relapses rendering the illness progressive to worse outcomes, a concept of which is compatible with neurotoxicity. Therefore, relapse prevention is of utmost clinical relevance. Methods In this review, we aim to put relapse into clinical context in the realm of natural history of, or heterogeneity in, schizophrenia and summarize risk factors of relapse. We discuss how to effectively 'define' relapse in schizophrenia and recent meta‐analytic studies on this topic to highlight the importance of continuous antipsychotic treatment. Results The following issues emerged: 'How low maintenance antipsychotic dosage could be?', 'How extended dosing could be?', 'Who could be successfully withdrawn from antipsychotics?' and 'How relapse could be defined in the first place?' The question in particular is how better to deliver antipsychotics at the lowest possible, whereby dose and dosing interval are relevant. While ongoing antipsychotic treatment is the rule, recent works are pointing to a possibility of lower dosage in the maintenance phase of the illness. Conclusions Bearing in mind that suboptimal adherence and withdrawal from antipsychotics are an established and unequivocal risk factor for relapse, further investigations are certainly needed to explore user‐friendly manner of psychopharmacotherapy to prevent relapse in schizophrenia. Copyright © 2014 John Wiley & Sons, Ltd.